Differences between vertical jumps in elite female volleyball players. Reasons for lack of differences - Joksimovic, M.; D'Angelo, S.; Eler, N.; Karisik, S.; Zlojutro, N.; Latino, F.; Tafuri, D. (Trends in Sport Sciences, 2024)
Introduction: Squat jumps (SJ) and countermovement jumps (CMJ) are commonly used as tests to assess power output of lower extremities.